PENGALAMAN HIDUP DAN KENDALA KOMUNIKASI DARI KELUARGA EKSPATRIAT DAN PERKAWINAN CAMPURAN DI KOTA METROPOLITAN JAKARTA -INDONESIA - Juwono Tri Atmodjo (Universitas Mercu Buana, 2018)
A cultural identity is adopted by a person that governs the relationships, lifestyle, and life that should be adhered to and rooted in ethnic members in ways of thinking, ways of life, and ways to overcome problems. What are the views, life experiences and constraints of communication from expatriate families and mixed marriages in the Metropolitan City of Jakarta, Indonesia. Case study with interviews with resource persons with the results and conclusions that (1) Ethnic values in a mixed marriage between American-Sundanese and English-Sundanese; open family, adapting culture from outside namely America through close family, papa and close family. (2) Jakarta-Italy Ethnic Couples (nations), more Chinese culture is absorbed especially language, trade spirit and religious rituals, but there are also spirits obtained from Italian parents. (3) Sicilia feels uncomfortable if called